2020
DOI: 10.1088/1361-6501/abc3de
|View full text |Cite
|
Sign up to set email alerts
|

Optimization measurement for the ballscrew raceway profile based on optical measuring system

Abstract: Given that the ballscrew raceway profile directly affects the service characteristics and precision retention of ball screws, this paper proposes an optimized continuous measuring method for the ballscrew raceway profile, without the need to adjust the sensor for the measurement of each raceway. Based on a comparison with existing measuring methods and principles, an optical measuring system is constructed, in which installation errors in the LED sensor and the linear calibration system, together with the stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…At present, many relevant scholars at home and abroad have conducted research on this subject and have already formed a relatively complete thread detection system, as in [3]- [8], which can be described as follows: First, the original image of the thread profile by CCD or other optical camera is captured, then the features of thread profile based on image processing techniques such as filtering, boundary extraction and curve fitting are extracted, and finally the parameters are measured from the acquired features such as the thread profile, which are considered as the result of detection. Min and Zhao respectively designed a non-contact thread parameter measurement system based on machine vision to support efficient and accurate measurement of the thread contact angle, as in [9], [10]; Rao et al summarized the image processing technology and computer vision algorithms currently used for external thread detection, as in [11]; Senthilnathan used a diffuse reflection light source to obtain a thread profile projection, and proposed a profile processing algorithm to estimate the thread parameters, as in [12]; Chen et al integrated the photoelastic effect and an image processing algorithm to measure the contact angle of the ball screw, as in [13]; Li et al proposed a Res Unet-based thread edge recognition method that eliminates the need for thread area calibration and identifies the thread edge in a complex environment, as in [14]; Chen took the possible thread shape distortion during CCD shooting into account, and gave a corresponding compensation algorithm for the image distortion on the optical angle, as in [15]. However, the above solutions are only applied to the detection of ordinary threads with a linear profile, while the Journal homepage: https://content.sciendo.com thread profile of the ball screw is a curve, which is more difficult to detect.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many relevant scholars at home and abroad have conducted research on this subject and have already formed a relatively complete thread detection system, as in [3]- [8], which can be described as follows: First, the original image of the thread profile by CCD or other optical camera is captured, then the features of thread profile based on image processing techniques such as filtering, boundary extraction and curve fitting are extracted, and finally the parameters are measured from the acquired features such as the thread profile, which are considered as the result of detection. Min and Zhao respectively designed a non-contact thread parameter measurement system based on machine vision to support efficient and accurate measurement of the thread contact angle, as in [9], [10]; Rao et al summarized the image processing technology and computer vision algorithms currently used for external thread detection, as in [11]; Senthilnathan used a diffuse reflection light source to obtain a thread profile projection, and proposed a profile processing algorithm to estimate the thread parameters, as in [12]; Chen et al integrated the photoelastic effect and an image processing algorithm to measure the contact angle of the ball screw, as in [13]; Li et al proposed a Res Unet-based thread edge recognition method that eliminates the need for thread area calibration and identifies the thread edge in a complex environment, as in [14]; Chen took the possible thread shape distortion during CCD shooting into account, and gave a corresponding compensation algorithm for the image distortion on the optical angle, as in [15]. However, the above solutions are only applied to the detection of ordinary threads with a linear profile, while the Journal homepage: https://content.sciendo.com thread profile of the ball screw is a curve, which is more difficult to detect.…”
Section: Introductionmentioning
confidence: 99%
“…And the model proposed was compared with the Wei model [7] from the perspective of prediction accuracy. Wang [17] et al studied the raceway profile for the BS, indicating that measuring basis is an influence factor of the raceway error on positioning precision. Zhao and Lin [18] et al studied the accuracy degradation behavior of double-nut ball screws due to raceway wear based on fractal theory [16].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the actual contact area between the ball and the raceway, based on the fractal theory, Liu and Ma et al 25 studied the mechanism of the BS accuracy degradation and compared the prediction accuracy to the Wei model results. 16 Wang et al 26 studied the raceway profile for the BS and demonstrated that measuring basis was one of the key influence factors of the raceway error on positioning precision. Zhao and Lin 27 studied the accuracy degradation behavior and accuracy prediction of the double-nut BS, due to raceway wear, based on fractal theory.…”
Section: Introductionmentioning
confidence: 99%